Attraction as a synergistic factor in interpersonal relationships and its psycho-bioenergetic significance [Аттракция как синергизуючий фактор в межличностных взаимоотношениях и ее психо-биоэнергетическое значение] (in Russian) - Іванченко, Андреянна Олексіївна; Иванченко, Андреянна Алексеевна; Ivanchenko, Andreyanna (Кам’янець-Подільський: Аксіома, 2010)
The paper is devoted to the study of attraction’s positive influence like a circulating beneficial psycho-bioenergetic stream for the establishment of creative interpersonal interrelations. It has been determined that the attraction activation is caused by the available person’s inclinations to the spiritual development and his tendency to the self-growth. The direct proportional dependence of the creativity development on the intensity of attractive interpersonal manifestations has been revealed. Стаття присвячена вивченню позитивного впливу атракції як циркулюючого благодатного психо-біоенергетичного потоку на встановлення креативних міжособистісних взаємин. Установлено, що включення атракції обумовлюють наявні у людини задатки духовного розвитку та його тенденція до саморосту. Виявлена прямопропорційна залежність розвитку креативності від інтенсивності атрактивних міжособистісних проявів.
Keywords: атракція; креативність; біоенергія; духовний розвиток